URGENSI PEMBUATAN PERJANJIAN PENGIKATAN JUAL BELI DALAM PROSES JUAL BELI TANAH - Chrisdanty, Febry; Wahyulina, Diah (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2025)
Land is a valuable asset that can be owned by legal subjects. Owning land can be done in several ways, one of which is through the buying and selling process. Legal transfer of land rights can only be done by making a Sale and Purchase Deed (AJB) made before the Land Deed Making Officer (PPAT). Making an AJB all administrative requirements both related to the subject and object are complete. In the field there are several conditions that result in the requirements for making an AJB not being able to be done, so there is a deed called a Sale and Purchase Binding Agreement (PPJB). PPJB is a preliminary agreement made to bind the seller and buyer, until an AJB can be made. PPJB and AJB are different, but many people still understand the two to be the same. The purpose of this study is to determine the position of PPJB in the land buying and selling process, and to analyze the differences between PPJB and AJB. The formulation of the problem raisedare (1) What is the position of PPJB in the process of buying and selling land and (2) What are the differences between PPJB and AJB? This paper is a type of empirical legal research, with an interview research approach method and questionnaire distribution, and using a descriptive analysis method. The results of this are (1) The position of PPJB and AJB is different in the process of buying and selling research land, (2) The differences between PPJB and AJB are as follows. PPJB is a preliminary agreement used to bind the parties and has no legal effect on the transfer of a land right, while AJB can prove the transfer of land rights made by the parties before a PPAT. Keywords: Binding, Sale and purchase, Agreement, Land.